Radiocarbon bomb-peak signal in tree-rings from the tropical Andes register low latitude atmospheric dynamics in the Southern Hemisphere - Ancapichun, Santiago; De Pol Holz, Ricardo Hernán; Christie, Duncan A.; Santos, Guaciara M.; Collado-Fabbri, Silvana; Garreaud, Rene; Lambert, Fabrice; Orfanoz-Cheuquelaf, Andrea; Rojas, Maisa; Southon, John; Turnbull, Jocelyn C.; Creasman, Pearce Paul (My University, 2021)
South American tropical climate is strongly related to the tropical low-pressure belt associated with the South American monsoon system. Despite its central societal role as a modulating agent of rainfall in tropical South America, its long-term dynamical variability is still poorly understood. Here we combine a new (and world's highest) tree-ring C-14 record from the Altiplano plateau in the central Andes with other C-14 records from the Southern Hemisphere during the second half of the 20th century in order to elucidate the latitudinal gradients associated with the dissemination of the bomb C-14 signal. Our tree-ring C-14 record faithfully captured the bomb signal of the 1960's with an excellent match to atmospheric C-14 measured in NewZealand but with significant differences with a recent record from Southeast Brazil located at almost equal latitude. These results imply that the spreading of the bomb signal throughout the Southern Hemisphere was a complex process that depended on atmospheric dynamics and surface topography generating reversals on the expected north-south gradient in certain years. We applied air-parcelmodeling based on climate data to disentangle their different geographical provenances and their preformed (reservoir affected) radiocarbon content. We found that air parcel trajectories arriving at the Altiplano during the bomb period were sourced i) from the boundary layer in contact with the Pacific Ocean (41%), ii) fromthe upper troposphere (air above the boundary layer, with no contact with oceanic or continental carbon reservoirs) (38%) and iii) fromthe Amazon basin (21%). Based on these results we estimated the Delta C-14 endmember values for the different carbon reservoirs affecting our recordwhich suggest that the Amazon basin biospheric C-14 isoflux could have been reversed fromnegative to positive as early as the beginning of the 1970's. Thiswould imply amuch faster carbon turnover rate in the Amazon than previouslymodelled. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: radiocarbon; tree-rings; southern hemisphere; carbon reservoir effect; atmospheric circulation